2021
DOI: 10.1007/s42399-021-00896-2
|View full text |Cite
|
Sign up to set email alerts
|

International Scientific Collaboration Is Needed to Bridge Science to Society: USERN2020 Consensus Statement

Abstract: Scientific collaboration has been a critical aspect of the development of all fields of science, particularly clinical medicine. It is well understood that myriads of benefits can be yielded by interdisciplinary and international collaboration. For instance, our rapidly growing knowledge on COVID-19 and vaccine development could not be attained without expanded collaborative activities. However, achieving fruitful results requires mastering specific tactics in collaborative efforts. These activities can enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results of our research have important clinical and practical implications, since again it was observed that vulnerable populations, such as people with ID, suffer many consequences from critical situations such as the COVID-19 pandemic [ 12 , 57 , 58 , 59 ]. In fact, the study by Cuschieri and Grech [ 57 ] observed that those with non-communicable diseases had a 6.55% higher risk of COVID-19 infection and often required hospital admission, mainly because of their vulnerability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of our research have important clinical and practical implications, since again it was observed that vulnerable populations, such as people with ID, suffer many consequences from critical situations such as the COVID-19 pandemic [ 12 , 57 , 58 , 59 ]. In fact, the study by Cuschieri and Grech [ 57 ] observed that those with non-communicable diseases had a 6.55% higher risk of COVID-19 infection and often required hospital admission, mainly because of their vulnerability.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the COVID-19 pandemic offers us the opportunity to promote health and social policies in vulnerable groups through interdisciplinary and biopsychosocial approaches, and indeed international collaboration, and the opportunity to understand where to act and what to modify. As a result, these vulnerable people will not be more affected in future critical situations because of their challenging conditions, diagnoses, or chronic diseases [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…development [5]. The academic community has recently emphasized the importance of working together in research and development [6,7].…”
Section: Clinical Medicine Reviewmentioning
confidence: 99%
“…Collaborating with international researchers provides access to experts, resources, and funding and enhances productivity and visibility. Borderless scientific mentorship supports young students [5].…”
Section: Clinical Medicine Reviewmentioning
confidence: 99%
“…But another thinking is going to be formed that this specializing is not completely ideal, and the holistic view could be beneficial to better understanding the world and science. Some international scientific collaborations and networks of scientists, like Universal Scientific Education and Research Network (USERN), follow this idea dealing with facilitating borderless science . Therefore, it seems that integration of the atomistic and holistic views would create the future of science.…”
mentioning
confidence: 99%